Visitor Loyalty Analysis of Lake Toba Tourism Destination through Integrated Marketing Communication - Butarbutar, Novita; Setyawati, Christina Yanita; Sinaga, Onita Sari; Doloksaribu, Winda Sri Astuti; Sudirman, Acai (Sekolah Tinggi Ilmu Ekonomi AMM, 2023)
This study analyzes the model of increasing visitor loyalty to Lake Toba tourist destinations through destination image management, experiential marketing and integrated marketing communication. The sampling method used in this study is the convenience sampling method. The number of samples analyzed was 160 Lake Toba tourism visitors. Data collection techniques using observation, interviews, questionnaires and documentation. The data analysis method used is Partial Least Square (PLS). The results of the data analysis concluded that destination image, experiential marketing, and integrated marketing communication (IMC) have a positive and significant effect on visitor loyalty. The implications of this research explain that Lake Toba tourism actors need to measure the image of the destination regularly, the effectiveness of experiential marketing campaigns, and the impact of IMC on visitor loyalty is significant. This data can help management understand trends, identify opportunities for improvement, and evaluate the success of implemented strategies. In addition, Lake Toba tourism actors need to conduct training and develop employee capabilities to be more skilled in communicating and serving tourist visitors. Employees and staff interacting directly with visitors must be trained to provide friendly, informative service and help with visitor complaints.